2015
DOI: 10.1177/0840470415617404
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of the Saskatchewan Leadership Program

Abstract: The Saskatchewan Leadership Program (SLP) was developed based on the LEADS framework and aligned with Lean management to build leadership renewal and sustainability conducive to transformational change in the Saskatchewan health system. This article describes the development, implementation, and evaluation of the SLP, including experiences and lessons learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…self-development emerged as a central requirement for Lean transitions in health care, with 13 research teams identifying it as a core principle. To successfully lead Lean transitions, health-care leaders need to develop new skills and competencies in Lean[26,35,36]. Mutwiri et al[36] identified specific skills and competences including awareness of one's own strengths, vision, and abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…self-development emerged as a central requirement for Lean transitions in health care, with 13 research teams identifying it as a core principle. To successfully lead Lean transitions, health-care leaders need to develop new skills and competencies in Lean[26,35,36]. Mutwiri et al[36] identified specific skills and competences including awareness of one's own strengths, vision, and abilities.…”
mentioning
confidence: 99%
“…To successfully lead Lean transitions, health-care leaders need to develop new skills and competencies in Lean[26,35,36]. Mutwiri et al[36] identified specific skills and competences including awareness of one's own strengths, vision, and abilities. Leaders need to develop these personal capabilities and demonstrate character so that they may effectively manage others and address the dynamics of change.…”
mentioning
confidence: 99%